THE LEGAL STANDING OF A LEASING AGREEMENT INVOLVING AN OBJECT ORIGINATING FROM A LEASE AGREEMENT - Vernandito Sudharta Raftua Tampubolon; Wardani Rizkianti (RADJA PUBLIKA, 2025)
The legal standing of leasing agreements involving objects derived from lease agreements continues to pose challenges in Indonesian legal practice, particularly when the party initiating the leasing agreement in Indonesian legal practice, particularly when the party initiating the leasing agreement is not the lawful owner of the object. This situation creates ambiguity regrading the legal status of the agreement and has the potential to harm good faith parties. This study adressees the issue of the legal position of leasing agreements involving objects not lawfully owned an lessor, moreover, the legal protection available to the lessee in such circumstances. The study is normative juridical study utilizing a qualitative analysis approach. Results of research indicate that leasing agreements involving objects not legally owned by the lessor are at conflict also principle ownership in civil law an may be subject to annulment. Legal protection for the leese can be granted through recognition as a good faith party, provided that it can be proven the leese was unaware of any defect in the owneship of the leased object. Outcomes of research is revealed needed strengthen regulations and apply the principle of due diligence in the execution of leasing agreements, particularly in verifying ownership of the leased object prior to the agreement being made.